The Komunikasi Pemasaran Agen Perisai BPJS Ketenagakerjaan - adha, ikhsan fauzi; Wulandari, Margareta; Adzka, Nadia (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2025)
The BPJS Ketenagakerjaan program has low participation rates, particularly in the Informal Sector Workers (BPU) program. Informal sector workers can register as participants to obtain the same rights as formal sector workers. Increasing the number of participants requires effective marketing communication, especially in order to inform potential participants. Shield agents use personal selling to attract participants. This study aims to determine the marketing communication applied by Shield Agents in their efforts to increase participant enrollment in the informal sector. The study uses a qualitative approach with a phenomenological approach and data collection techniques, including interviews, observation, and documentation. The research results are divided into six stages. First, prospecting by identifying targets from the immediate environment and community. Second, the pre-approach is conducted by introducing product differences and building trust through ID cards and assignment letters. Third, presentations, brochures, and testimonials explain the benefits and fees. Fourth, objection handling involves exploring the reasons for objections and providing solutions. Fifth, closing focuses on convincing potential participants and assisting with registration. Sixth, follow-up aims to maintain loyalty and measure participant satisfaction. This strategy is expected to increase participant acquisition significantly.